2016
DOI: 10.3109/01676830.2016.1139592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optic nerve sheath fenestration for idiopathic intracranial hypertension on retinal nerve fiber layer thickness

Abstract: The objective of the study was to evaluate whether optic nerve sheath fenestration in patients with idiopathic intracranial hypertension was associated with improvement in visual field pattern deviation and optical coherence tomography retinal nerve fiber layer thickness.The records of 13 eyes of 11 patients who underwent optic nerve sheath fenestration were reviewed. The subjects were patients of a clinical practice in Dallas, Texas. Charts were reviewed for pre- and postoperative visual field pattern deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…After decompressive surgery, axonal swelling may decrease and postoperative peripapillary RNFL thickness might reflect the amount of true optic nerve atrophy. A previous study that investigated the effect of optic nerve decompression using optic nerve sheath fenestration in patients with intracranial hypertension on peripapillary RNFL thickeness also revealed that the average RNFL thickness decreased to 103 μm from 114 μm postoperatively [28]. Also, delayed ganglion cell atrophy could lead to a progressive decrease in peripapaillary RNFL thickness postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…After decompressive surgery, axonal swelling may decrease and postoperative peripapillary RNFL thickness might reflect the amount of true optic nerve atrophy. A previous study that investigated the effect of optic nerve decompression using optic nerve sheath fenestration in patients with intracranial hypertension on peripapillary RNFL thickeness also revealed that the average RNFL thickness decreased to 103 μm from 114 μm postoperatively [28]. Also, delayed ganglion cell atrophy could lead to a progressive decrease in peripapaillary RNFL thickness postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…Thirdly, there is a lack of sensitive and objective predictors for monitoring relapses and remissions of IIH . Furthermore, there is no consensus on how long medical therapy of IIH should be continued and when a decision for surgical intervention should be made .…”
Section: Introductionmentioning
confidence: 99%
“… 43 When patients develop optic atrophy in the chronic period, RNFL thinning is already an expected outcome. 44 …”
Section: Discussionmentioning
confidence: 99%